1988
DOI: 10.1084/jem.168.2.777
|View full text |Cite
|
Sign up to set email alerts
|

Induction of arthritis in monkeys by immunization with type II collagen.

Abstract: Immunization of two cynomolugus and three rhesus monkeys with purified type II collagen resulted in the development of polyarthritis. Arthritis first became clinically apparent 7 wk after primary immunization and persisted for 16 mo. Radiologic examination of the limbs demonstrated soft tissue swelling with severe joint destruction including loss of cartilage and bone. Involved joints eventually became ankylosed with permanent loss of some motion. All of the monkeys developed a response to the immunizing colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…Collagen-induced arthritis (CIA) is an experimental model of autoimmune disease, which can be induced in mice (Yoo et al, 1988), rats (Cuzzocrea et al, 1999a,b) and primates (Trentham, 1982) by immunization with type II native articular cartilage collagen (CII). The joint pathology associated with CIA is similar to the one observed in patients with RA (Stuart et al, 1982a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen-induced arthritis (CIA) is an experimental model of autoimmune disease, which can be induced in mice (Yoo et al, 1988), rats (Cuzzocrea et al, 1999a,b) and primates (Trentham, 1982) by immunization with type II native articular cartilage collagen (CII). The joint pathology associated with CIA is similar to the one observed in patients with RA (Stuart et al, 1982a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Both B cell (5,6) and T cell (7)(8)(9) immunity to CII have been reported, and the presence of CII Abs and CII-specific T cells in arthritic joints has been demonstrated (6,9,10). Additionally, a number of animal models have been described in which immunization with CII elicits an autoimmune arthritis that shares many similarities with RA (11)(12)(13)(14)(15)(16). In recent years, several mouse models have been developed in which the susceptibility to collagen-induced arthritis (CIA) is dependent on the transgenic expression of HLA-DR alleles associated with susceptibility to RA (12,13,17).…”
mentioning
confidence: 99%
“…Studies in RA patients have shown antibody and T cell activity directed to intact and denatured CII (36)(37)(38). Furthermore, injection of heterologous CII into rats, mice, and monkeys results in joint inflammation and pathology with considerable similarity to human RA (35,39,40). Collagen-induced arthritis (CIA) is linked to MHC class II genes, similar to RA (41).…”
Section: Introductionmentioning
confidence: 99%